Mastitis in lactating women: A case report - Yulizawati, Yulizawati; Silmi, Harridhil; Intasir, M. Pemberdi (Journal of Midwifery, 2023)
Mastitis, or breast inflammation, is classified as either non-lactational or lactational. Mastitis that occurs during lactation is the most prevalent type. Worldwide, only 50% of women are able to breastfeed for six months. It could be the result of an inflammatory breast condition, such as puerperal mastitis or milk stasis, which in certain cases requires supplementation or stopping breastfeeding entirely. We describe a complicated case of a primipara patient who appeared three months after giving birth with lactational mastitis. In this review, we emphasize how crucial multidisciplinary teamwork using Midwifery care is to accurate diagnosis and successful treatment. We go over the usage of oral antibiotics and provide examples of the kind of client support needed to help patients heal and successfully breastfeed during the postpartum phase. Giving the mother the right care and guidance is therefore crucial since poorly managed mastitis can result in an early end to breastfeeding and cause suffering for both the mother and the child.